Time to pay attention: Elder abuse in the COVID-19 Pandemic Era - Nader Aghakhani; Kazhal Mobaraki; Marzieh Hossini; Jamal Ahmadzadeh (Global Journal of Rare Diseases - Peertechz Publications, 2021)
COVID 19 pandemic has presented an opportunity for health care providers to expand their understanding of risks of using neglectful or abusive behavior to the elder during this time, and consider incorporating studies related to this challenge. Individuals experiencing caregiving concern and stress about whether their loved ones' needs will be met should be considered. They should be more open to share their uncomfortable experiences. Being aware of the problems of older adults and their caregivers is critical to helping them thrive and survive during this pandemic. Addressing increased risks, attending to mental health needs, and connecting older adults to caregiving and providing financial resources can all help the old patients and their loved ones to avoid violent and abusive situations and be safer.